Pelaksanaan Mosintuwu Mamporewu Balita Stunting di Desa Bulili dan Kageroa, Kabupaten Poso - John Yus Madoli; Syahmaeni Syahmaeni; Askir Askir; Kadar Ramadhan (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
The role of the Local Government Organizations (OPD) in the district is very important in efforts to reduce the incidence of stunting in the region. One of the efforts made by the Regional Development Planning Agency (Bappelitbangda) of Poso District is to carry out the Mosintuwu Mamporewu program. The aim of this program is to provide intervention to toddlers who suffer from stunting. The program was carried out in the villages of Bulili and Kageroa, Poso District. This program was conducted for 3 months, from October 2022 to December 2022. The activities carried out included socialization of accelerated stunting reduction with stakeholders and relevant parties, including providing assistance. The results of this program showed a decrease in the number of stunted children from 6 to 5. We hope that the village government will ensure that the convergence funding for stunting reduction through mandatory village funds is carried out in accordance with existing regulations, and we also hope that the health center will actively provide further assistance.